Articulating natural resource abundance, economic complexity, education and environmental sustainability in MENA countries: Evidence from advanced panel estimation. (January 2023) - Saud, Shah; Haseeb, Abdul; Zafar, Muhammad Wasif; Li, Huiyun
Abstract: The most crucial area of intense debate among economists to prevent environmental deterioration due to global climate change is structural transformation and natural resource management. However, economic complexity, natural resource abundance, education and ecological sustainability relationships are unsatisfactorily investigated, with diverse findings are evidenced in the prior literature. Therefore, natural resource abundance, economic complexity, education, and environmental sustainability were analysed for "Middle East and North Africa" (MENA) nations from 1980 to 2020. The current research embraced the Westerlund cointegration, continuously updated fully modified (CUP-FM) and delivering consistent outcomes using the alternative specification of continuously updated bias-corrected (CUP-BC) and the Dumitrescu and Hurlin (DH) causality. The proposed models also incorporate variables that drive environmental degradation, such as financial development and economic growth. The empirical results confirm the negative long-run relationships of economic complexity with carbon dioxide emissions (CO2 emissions) and the ecological footprint. A one-point increase in economic complexity reduced CO2 emissions by 0.0081 points and the ecological footprint by 0.1152 points. In conjunction with all this, natural resource abundance is adversely related to CO2 emissions (0.0111) and the ecological footprint (0.0229). However, education, financial development and economic growth impede environmental deterioration by high CO2 emissions and the ecological footprint. The EKC phenomenon has been verified for MENA countries. Meanwhile, education and economic complexity cause CO2 emissions and vice versa, whereas natural resource abundance causes CO2 emissions without feedback. Hence, the outcomes encourage policy-makers to consider and embrace holistic economic-environmental green policies to achieve sustainable development in the region and cope with COP21. Highlights: Articulating Natural Resource Abundance, Economic Complexity, Education and Environmental Sustainability in MENA. Economic complexity and natural resource abundance boost environmental sustainability. Contrarily, education upsurge CO2 emissions and EFI. The EKC phenomenon is validated for MENA. Bidirectional causal links are established between education, CO2 emissions, and EFI.